ANALISIS PENATAAN KECAMATAN DI KABUPATEN SUMBA BARAT PROVINSI NUSA TENGGARA TIMUR - Deding Ishak (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2017)
This research has the objective to analyze and provide policy recommendations with regard to the arrangement of sub-districts in West Sumba. This study used tailor made method which directs a comprehensive study results become a major consideration for policy makers in the formulation of policy. In addition, to make the analysis more relevant to the needs of West Sumba district in settlement and regional development, the methods of tailor made method combined with the method of FGD (expert meetings) with the bureaucracy involved, and Techniques Delphi, which is one of the techniques stakeholder involvement in decision decision/policy by collecting opinions through questionnaires/checklists. The data were then analyzed using a qualitative approach to obtain in-depth and comprehensive understanding. The results showed that of the six sub districts that were analyzed, sub tanarighu a district that most deserves to bloomed. in addition to the recommendation of the researchers was Arrangement border enclave, Improved system of planning, the use of ICT in governance systems, and organizational management districts. Keywords: sub-districts, structuring the sub-district.